(untitled) (Bangladesh Journal of Botany, 2025)
Ephedra is a medicinal plant well known for its therapeutic properties, primarily attributed to its bioactive compounds. Recent studies have highlighted its antifungal potential, particularly against Aspergillus flavus, a phytopathogenic fungus responsible for aflatoxin production. However, studies on this topic remain limited. The present study aimed to investigate the anatomical adaptations of Ephedra altissima stems and to evaluate the antifungal activity of its flavonoid compounds. A detailed histological analysis was performed, complemented by an in silico study, which confirmed the strong antifungal activity of these compounds. These findings highlight the potential of Ephedra as a natural agent for managing fungal pathogens in both agriculture and healthcare. Bangladesh J. Bot. 54(4): 1005-1013, 2025 (December)